Paradise lost; a poem. - Milton, John, 1608-1674 (London, Printed for Sharpe by Whittingham, 1821)
In Paradise Lost, Milton produced a poem of epic scale, conjuring up a vast, awe-inspiring cosmos ranging across huge tracts of space and time. And yet, in putting a charismatic Satan and naked Adam and Eve at the center of this story, he also created an intensely human tragedy on the Fall of Man. Written when Milton was in his fifties blind, bitterly disappointed by the Restoration, and briefly in danger of execution, Paradise Lost's apparent ambivalence toward authority has led to intense debate about whether it manages to justify the ways of God to men, or exposes the cruelty of Christianity.
Volume [1]. Books I-VI -- Volume [2]. Books VII-XII.
Mode of access: Internet.
Keywords: Eve -- (Biblical figure); Adam -- (Biblical figure); Eve -- (Biblical figure) -- Poetry; Adam -- (Biblical figure) -- Poetry; Fall of man -- Poetry; Epic poetry; Poetry; Epic poetry